(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article extensively covers the adaptation of school children of young school age, their psychological and social development, and the role of teachers and parents. A child who comes to school for the first time experiences a number of psychological and moral difficulties in adapting to a new environment. Children’s adaptation to new norms and rules at school, establishing relationships with peers, and forming positive relationships with teachers require voluntary actions from the child.